Assessment of Water Resilience Index Due to the Technical Instruction - Deby, Rachmat; Limantara, Lily Montarcih; Dermawan, Very; Wahyuni, Sri (Journal of Ecohumanism, 2025)
This research intends to assess the water resilience in Lasolo Watershed that will be as the validation value in building the mathematical model of water resilience performance index based on the scientific study. This research is conducted in the Lasolo Watershed, Southeast Sulawesi. The Lasolo Watershed is in the Lasolo Konawa River region. Lasolo River consists of 18 sub-watersheds. The assessment is carried out based on the 5 aspects that are conservation of water resources (3 indicators and 17 sub-indicators), utilization of water resources (6 indicators and 27 sub-indicators), damage control (3 indicators and 12 sub-indicators), participations of society (4 indicators and 16 sub-indicators), and information system of water resources (3 indicators and 6 sub-indicators). The methodology consists of analyzing the score of each sub-indicators and total scores of each indicator in every dimension, analyzing total of maximum value in every dimension, determining the weight of each dimension, analyzing the end score of dimensions, analyzing the score of Water Resilience Index (IKtA) and the score total, and analyzing the value of water resilience index. The result shows that the 17 sub-watersheds indicate the condition of water resilience are prone (score: 2.1-3.0) and 1 sub-watershed indicates the condition of water resilience is danger (score 0.0-2.1).